Pengelolaan Keuangan Masjid: Studi Empiris pada Masjid Al Furqan Kecamatan Lubuk Begalung Kelurahan Pulau Aia Nan XX Kota Padang - Rizki, Muhammad Fadhillah; Deviani, Deviani (Universitas Negeri Padang, 2024)
The specificity of the problem formulation is how to manage mosque finances at the Al-Furqan Mosque. The aim of the research results is to find out the dynamics of the financial management practices of the Al-Furqan Mosque. The method used is a qualitative method using an ethnomethodological approach. This research is different from previous research because specifically this research is related to the financial management of mosques in the month of Ramadhan because in the month of Ramadhan there are many activities carried out at the Al Furqan Mosque such as Taraweh, Ramadhan Islamic Boarding School, Makjlis Taklim, Wirid Pemuda and other activitie and the respondents in this study are mosque administrator and people that around the mosque. The conclusion of this research is that the financial management of the mosque has been running well, this is shown by the active role of the congregation directly in mosque activities, the programs have been running effectively, this can be seen from the active role of the leader in motivating all administrators to be able to serve the mosque congregation better by providing useful programs for mosque congregations and very clear cash flow reports. The suggestions given by researchers for further research are to carry out deeper research, both in terms of interviews with informants and data processing with more references. So that the information needed by researchers is more abundant and can be developed.